Complex Dietary Interventions to Slow Rates of Aging - Aksenov, Vadim (My University, 2014)
Aging erodes motivation, cognition, sensory modalities and physical capacities, effectively depleting quality of life. Declining sensory, cognitive and motor function are reliable biomarkers of aging and mortality risk. These declines are associated with dysregulation of systemic and cellular processes. We developed a complex dietary supplement (DSP) designed to ameliorate five mechanisms of aging (oxidative processes, inflammation, mitochondrial function, insulin resistance and membrane integrity). Remarkably, normal mice fed the DSP retained youthful functionality into old ages, reflecting slower aging rates. Marked improvements in motor function, memory capacity, spatial learning, muscle strength, visual acuity, olfaction, fecundity and important behavioral functions were observed in aging supplemented mice. Conversely, untreated control animals showed age-related declines in all of the above. Functional improvements were associated with reduced oxidative damage, elevated mitochondrial activity, positive cellular energy balance, improved glucose tolerance, boosted neurotransmitters, greater synaptic density and higher neuronal numbers throughout the brain. A 30% reduction in cancer rates was also documented for DSP treated p53+/- mice. The vast functional benefits greatly exceed the modest longevity extension (11%) in normal supplemented mice. For aging humans, maintaining functionality and performance into later years may provide greater socioeconomic and health benefits than simply prolonging lifespan. Implications of these findings extend to common age-related pathologies including dementia and neurodegenerative diseases, diabetes, cancer, sarcopenia and age-related macular degeneration. Although identifying the role of specific ingredients remains outstanding, results provide proof of principle that complex dietary cocktails can powerfully ameliorate biomarkers of aging and modulate mechanisms considered ultimate goals for aging interventions.
Keywords: Aging and Anti-Aging; Complex Dietary Supplement; Motor Cognitive Sensory Function; Free Radicals Oxidative Damage and Mitochondria; Brain Neuroprotection Neurodegenerative Disease; Blood Glucose Cancer p53 and Growth; Behavioral Neurobiology; Biology; Complex Mixtures; Other Nutrition; Systems and Integrative Physiology; Behavioral Neurobiology